2004
DOI: 10.1073/pnas.0406133102
|View full text |Cite
|
Sign up to set email alerts
|

S-nitroso proteome ofMycobacterium tuberculosis: Enzymes of intermediary metabolism and antioxidant defense

Abstract: The immune response to Mycobacterium tuberculosis (Mtb) includes expression of nitric oxide (NO) synthase (NOS)2, whose products can kill Mtb in vitro with a molar potency greater than that of many conventional antitubercular agents. However, the targets of reactive nitrogen intermediates (RNIs) in Mtb are unknown. One major action of RNIs is protein S-nitrosylation. Here, we describe, to our knowledge, the first proteomic analysis of S-nitrosylation in a whole organism after treating Mtb with bactericidal con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
141
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 160 publications
(145 citation statements)
references
References 55 publications
4
141
0
Order By: Relevance
“…These new thiols are then marked by introduction of a mixed-disulfide bond with a biotin-tagging reagent, captured on immobilized avidin, and selectively released from avidin by reduction of the disulfide linker. Several laboratories have used the biotin-switch method in combination with 1D or 2D PAGE and in-gel trypsinolysis for identification of SNO proteins by mass spectrometry (10)(11)(12)(13)(14). To extend the capability of this approach, we introduced a proteolytic digestion step before avidin capture.…”
Section: Snosid a Proteomic Methods For Identification Of Cysteine S-mentioning
confidence: 99%
“…These new thiols are then marked by introduction of a mixed-disulfide bond with a biotin-tagging reagent, captured on immobilized avidin, and selectively released from avidin by reduction of the disulfide linker. Several laboratories have used the biotin-switch method in combination with 1D or 2D PAGE and in-gel trypsinolysis for identification of SNO proteins by mass spectrometry (10)(11)(12)(13)(14). To extend the capability of this approach, we introduced a proteolytic digestion step before avidin capture.…”
Section: Snosid a Proteomic Methods For Identification Of Cysteine S-mentioning
confidence: 99%
“…For instance, DLDH was found to be modified by 4-hydroxynonenal (HNE) in the ventilatory muscles of rats challenged by lipopolysaccharide (Hussain, et al, 2006), and found to be nitrosylated in rat liver (Foster and Stamler, 2004) and in Mycobacterium tuberculosis (Rhee, et al, 2005). Because DLDH activity was not measured in these studies, it is not yet known whether or not the HNE modification or nitrosylation had any significant inhibitory effects.…”
Section: Discussionmentioning
confidence: 99%
“…Whereas many enzymes are subject to inhibition by peroxynitrite, the contribution of tyrosine nitration, S-nitrosation, and other mechanisms to inactivation varies considerably [67][68][69][70]. DTT only partially protected against PDHC inhibition, suggesting that tyrosine nitration is the primary mechanism of inactivation.…”
Section: Nih-pa Author Manuscriptmentioning
confidence: 99%